Os desafios do ensino superior na revolução digital - Lúcio Filho, Laurentino (2015)
This research deals with the proposal of the incorporation of new information and communication technologies - NICTs - in higher education, is based on the improvement of teaching quality by simplifying complex tasks, reducing the distance and hence the time, thus improving work efficiency. At first glance, the contact of the actors with the NTICs in this process often reveals itself without the existence of an inclusive methodology because the action of these technologies by higher education institutions seems to result only on attempts to adapt to social demands and marketing in new contexts produced by the digital revolution, making this very misshapen inclusive process, and in turn, limiting the positive effect on the results. This paper discusses the process of incorporating technologies in higher education, seeking to evaluate the reconciliation of traditional methodologies and aspects of their current transformations, hoping to offer subsidies for understanding which are currently the challenges experienced in higher education and how the IES have sought to address them, outlining roughly the current profiles of its actors. To develop this work we chose to use the theories and methodologies of researches carried out by Manuel Castells (2013), Pierre Levy (2010), John B. Thompson (2014). These were accompanied by researches in the areas of philosophy education, especially Edgar Morin (2013) and Maurice Tardif (2011), supplemented by extensive bibliography with ancillary issues. The extensive bibliography that we used helped us to develop a critical reflection on the challenges that are present in high education, particularly in Brazil, and from that reflection, brought up proposals formulated by authors who are researching on the same line of this work, proposals which are healthy and able to respond to the main current challenges. The research's results before of the higher education challenges has been identified that the crisis experienced by the institutions have as factors: the transition between institutional and emerging models. Furthermore, technological training or specialization of education professionals have been occurring through fragmented and diffuse modules, which makes the application of computer-mediated communication decontextualized with learning object. Finally, it presents as a diagnostic to overcome these challenges, the need to define the teach model, based on education reforms that combine linear thought with complex thought, making possible the identification of the new profiles that the institution and teacher may to have in the society